PERAN KEPEMIMPINAN KEPALA SEKOLAH MEMODERASI PENGARUH MOTIVASI KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU (Studi Pada Guru SMA Negeri Pati Kota di Kabupaten Pati) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze that school leadership moderates the effect of work motivation and organizational commitment to the performance of a high school teacher in the District City State Pati Pati. This study is the population of all teachers who work in Public High Schools in the City Pati Pati regency, amounting to 164 people used as a sample. Mechanical testing of the data used in this study include testing the validity of the factor analysis, and reliability testing with Cronbach alpha formula. The technique uses multiple regression analysis model of moderation Type Quasi. The results showed that; work motivation positive and significant impact on teacher performance, organizational commitment negatively affect the performance of teachers, school leadership does not affect the performance of teachers, school leadership weaken the influence of motivation to work on the performance of teachers, school leadership strengthen the influence of organizational commitment on teacher performance in high school country town in the district of Pati Pati. Keywords: work motivation, organizational commitment, school leadership, teacher performance.